STRATEGI INOVASI PEMBANGUNAN DESA TERTINGGAL DI ERA REVOLUSI INDUSTRI 4.0 DAN PERANANANNYA DALAM KESEHATAN MASYARAKAT - Muhammad Usamah Yusuf (CV. Adiba Aisha Amira, 2023)
This study was conducted to collect sufficient information on innovation strategies for underdeveloped village development in the era of industrial revolution 4.0 and its in public health. The method used in this study is a literature study that reviewed related journals to answer how innovative strategies for rural development are lagging behind in the era of Industrial Revolution 4.0. The results of this study suggest that the strategy for the development of vulnerable villages should be carried out in stages, calculations are required, and the assistance of all parties is required. All problems in each field must be developed in line with the changes in the era of Industrial Revolution 4.0. In addition to implementing innovation strategies, communities must balance this with computerization or digitization.